Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd001087.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Crisis intervention for people with severe mental illnesses

Abstract: Background A particularly difficult challenge for community treatment of people with serious mental illnesses is the delivery of an acceptable level of care during the acute phases of severe mental illness. Crisis intervention models of care were developed as a possible solution. Objectives To review the effects of crisis intervention models for anyone with serious mental illness experiencing an acute episode, compared with ‘standard care’. Search methods We updated the 1998, 2003 and 2006 searches with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 113 publications
2
71
0
15
Order By: Relevance
“…31 Las razones por las que un paciente recae son muy diversas, aunque se ha reportado que el índice de recaídas es mayor en los pacientes que sólo reciben tratamiento farmacológi-co en comparación con aquellos que recibieron tratamiento psicosocial y psicoeducación en conjunto con el tratamiento farmacológico. 15 Sin embargo, también se ha visto que muchos pacientes con esquizofrenia reciben medicación en las dosis preescritas y a pesar de eso presentan recaídas. 27 Las recaídas que mencionan los familiares que participaron en el grupo de discusión fueron provocadas por mal manejo o retiro de medicamentos.…”
Section: Las Recaídas Subsecuentes Y Las Continuas Crisisunclassified
See 2 more Smart Citations
“…31 Las razones por las que un paciente recae son muy diversas, aunque se ha reportado que el índice de recaídas es mayor en los pacientes que sólo reciben tratamiento farmacológi-co en comparación con aquellos que recibieron tratamiento psicosocial y psicoeducación en conjunto con el tratamiento farmacológico. 15 Sin embargo, también se ha visto que muchos pacientes con esquizofrenia reciben medicación en las dosis preescritas y a pesar de eso presentan recaídas. 27 Las recaídas que mencionan los familiares que participaron en el grupo de discusión fueron provocadas por mal manejo o retiro de medicamentos.…”
Section: Las Recaídas Subsecuentes Y Las Continuas Crisisunclassified
“…), ya que están implicados en la problemática de la enfermedad y se ven afectados por la carga que conlleva el cuidado de su familiar enfermo. Existen estudios sobre el tratamiento integral [15][16][17] que demuestran una notable mejoría en el autocuidado, la socialización, el apego terapéutico y en la mejoría de las relaciones familiares que normalmente están alteradas en el paciente con esquizofrenia.…”
Section: Necesidad De Atención Integralunclassified
See 1 more Smart Citation
“…While briefer follow-up looked promising, 4 this longer follow-up eventually found AO to do scarcely better than the CMHT for a lot more clinical effort and presumably, cost. 3 Early intervention for psychosis services, too, have had questionable benefits.…”
mentioning
confidence: 96%
“…A recent systematic review of crisis intervention for severe mental illness found just six studies evaluating the effect of community crisis teams on 984 patients and judged their methodology to be 'poor'. 4 These six studies excluded service users with alcohol or drug misuse, or those in danger of harming themselves or others, and so are atypical of populations managed by community teams in England.…”
mentioning
confidence: 99%